Association between otolin-1 and benign paroxysmal positional vertigo: A meta-analysis - Liu, Xiaoxia; Han, Kun; Zhou, Min; Wu, Yunqin (Frontiers in Neurology, 2022)
Background There is increasing research on the potential of inner ear proteins as serum biomarkers for the diagnosis and prognosis of various inner ear diseases. Among them, benign paroxysmal positional vertigo (BPPV) is the most common vestibular disease. Notably, otolin-1, an inner ear-specific protein, is detectable in the serum of most patients with BPPV patients. Therefore, we found a need to conduct this meta-analysis to determine the relationship between otolin-1 in serum and BPPV. Methods This meta-analysis was conducted by searching PubMed, EMBASE, Cochrane Library, Google Scholar, and China Network Knowledge Infrastructure databases for the eligible original studies in Chinese or English published between January 2010 and February 2022. Data were collected and pooled by using the mean differences (MDs) corresponding to 95% confidence intervals (CIs). Heterogeneity among these studies was assessed by using I2 statistics and the adopted fixed or random-effect mode thereafter. Egger's and Begg's tests were also used to assess the publication bias. Results This meta-analysis included six articles with a total of 585 participants. Serum otolin-1 levels were remarkably increased in patients with BPPV as compared to that in healthy controls (MD: 165.38, 95% CI: 110.13–220.64, p < 0.00001). However, Egger's and Begg's tests have indicated no publication bias, and the results were reliable based on the sensitivity analysis. Conclusion This meta-analysis indicated that there is a higher serum level of otolin-1 in patients with BPPV than in healthy controls. Therefore, otolin-1 may serve as a biomarker for the onset of BPPV.